Food Handling Concerns and Practices Among Patients With Underlying Medical Conditions Associated With COVID-19 Severity. (7th June 2021) - Trippel, Abbey; Granata, Frank; Weller, Daniel; Stump, Tammy; Carnethon, Mercedes; Kershaw, Kiarri; Lin, Annie
Abstract: Objectives: Concerns about COVID-19 transmission have led to greater engagement in unsafe food handling practices (i.e., practices that can cause illness due to chemical or microbial contamination of food). Despite public awareness that certain medical conditions exacerbate COVID-19 illness severity, little is known about whether these patients have unique concerns and/or engage in unsafe practices to prevent COVID-19 infection. We compared the concerns and practices between adults with and without underlying medical conditions associated with greater COVID-19 severity. Methods: An online survey was distributed among urban residents between July-August 2020 to inquire about food handling concerns and practices. Participants were included in the "higher-risk" group if they had ≥1 medical condition known to aggravate COVID-19 severity. Participants without any of these underlying medical conditions were included in the comparison group. Food handling concerns were rated on a 5-point scale (1 = never, 5 = always) and practices were determined using "yes/no" responses. Between-group differences in food handling beliefs and practices were analyzed with independent t-tests and Fisher's exact tests. Results: Participants ( n = 437) had a mean age of 34.2 ± 0.5 years. The higher-risk group ( n = 132) was more concerned about foodborne transmission of COVID-19, regardless of food vehicle, than the comparison group (all ps < 0.0001). The higher-risk group also washed produce with cleaning agents (e.g., soap, hydrogen peroxide) more frequently [3.1 ± 1.6 vs. 2.5 ± 1.7; P = 0.001]. Relative to the comparison group, the higher-risk group left perishable food items outside for >1 hour ( P < 0.0001) and washed raw meats with water and/or cleaning agents more often ( P = 0.0001), while washing their hands before food preparation less often ( P = 0.02). Conclusions: Those at higher risk of greater COVID-19 severity were more concerned with foodborne COVID-19 transmission and more frequently engaged in unsafe food handling practices than those without underlying conditions. Effective methods are needed to correct misinformation surrounding COVID-19 foodborne transmission, especially among those with underlying medical conditions. Funding Sources: This study was supported by a National Cancer Institute training grant.